The book of Jeremiah: an annotated bibliography - Thompson, Henry O. (ATLA bibliography series, 1996)
The Book of Jeremiah, surrounded by debate, remains stimulating with continuing literary output. This selective bibliography surveys some of this output and provides an overview of the vast literature. Each alphabetically arranged entry gives full bibliographic information and describes the contents or argument of the text. Thompson's introduction outlines the biblical material and some of the interpretive issues involved in the study of Jeremiah. The bibliography includes a list of abbreviations and is fully indexed by author, subject, and scriptual reference. Helpful appendixes provide listings of dissertations and these done on Jeremiah and journals including related material. The Book of Jeremiah: An Annotated Bibliography will prove to be important to religious scholars of both Judaism and Christianity, graduate and undergraduate students, and will be a valuable reference work for university, college, and religious libraries.